2005
DOI: 10.1631/jzus.2005.b0187
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and mechanism investigation on advanced reburning for NOx reduction: influence of CO and temperature

Abstract: Pulverized coal reburning, ammonia injection and advanced reburning in a pilot scale drop tube furnace were investigated. Premix of petroleum gas, air and NH 3 were burned in a porous gas burner to generate the needed flue gas. Four kinds of pulverized coal were fed as reburning fuel at constant rate of 1g/min. The coal reburning process parameters including 15%~25% reburn heat input, temperature range from 1100 °C to 1400 °C and also the carbon in fly ash, coal fineness, reburn zone stoichiometric ratio, etc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the present case, NO 2 is practically absent. NO originates mainly from the Zeldowich thermal process, [23][24][25] since the CO molecule does not contain N atoms, and when the gas mixture is sufficiently lean (E a ) 20% or more), the formation of radicals CH and HCN is not significant (Fenimore mechanism). [23][24][25][26][27][28][29] Moreover, thermal NO emissions are expected to decrease with lower flame temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present case, NO 2 is practically absent. NO originates mainly from the Zeldowich thermal process, [23][24][25] since the CO molecule does not contain N atoms, and when the gas mixture is sufficiently lean (E a ) 20% or more), the formation of radicals CH and HCN is not significant (Fenimore mechanism). [23][24][25][26][27][28][29] Moreover, thermal NO emissions are expected to decrease with lower flame temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…NO originates mainly from the Zeldowich thermal process, [23][24][25] since the CO molecule does not contain N atoms, and when the gas mixture is sufficiently lean (E a ) 20% or more), the formation of radicals CH and HCN is not significant (Fenimore mechanism). [23][24][25][26][27][28][29] Moreover, thermal NO emissions are expected to decrease with lower flame temperatures. Catalytic combustion is operated at lower temperature compared to the conventional flame combustion, thus reducing the formation of thermal NO x , which starts at about 1500 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…air flow carried out by the authors showed that calculated results of the calculations are in agreement with the model and often overlap. The perfectly stirred reactor is commonly used by researchers not only in the reburning process modelling, but also in other low-emission methods of calculating air recirculation, or air staging, which is evidenced in a large body of published studies (Adamczuk and Radomiak, 2010;Fan et al, 1998;Faravelli et al, 2001;Ljungdahl and Larfeldt, 2001;Luan et al, 2009;Szecowka et al, 2003;Wang et al, 2005;.…”
Section: Numerical Modellingmentioning
confidence: 99%